2015
DOI: 10.1126/scitranslmed.3010611
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human brain cancer infiltration ex vivo and in vivo using quantitative optical coherence tomography

Abstract: More complete brain cancer resection can prolong survival and delay recurrence. However, it is challenging to distinguish cancer from non-cancer tissues intraoperatively, especially at the transitional, infiltrative zones. This is especially critical in eloquent regions (e.g. speech and motor areas). This study tested the feasibility of label-free, quantitative optical coherence tomography (OCT) for differentiating cancer from non-cancer in human brain tissues. Fresh ex vivo human brain tissues were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
346
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(366 citation statements)
references
References 41 publications
14
346
3
3
Order By: Relevance
“…Such a qualitative link may verify that certain structures can be detected in both images, but remains indirect because it does not guarantee that each observed object or even the major part of it, indeed corresponds to, e. g., a brain cell. If the quantitative link between these novel images and fluorescence/H&E stained images can be established, it will facilitate and verify the interpretation of these novel images, and further strengthen their potential for real-time pathology of human brain tumors [6,21,24,25].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Such a qualitative link may verify that certain structures can be detected in both images, but remains indirect because it does not guarantee that each observed object or even the major part of it, indeed corresponds to, e. g., a brain cell. If the quantitative link between these novel images and fluorescence/H&E stained images can be established, it will facilitate and verify the interpretation of these novel images, and further strengthen their potential for real-time pathology of human brain tumors [6,21,24,25].…”
Section: Introductionmentioning
confidence: 93%
“…THG images of structurally normal and tumor tissues have been compared, not one-toone, with histopathological images of the same samples stained with hematoxylin and eosin (H&E) [6]. Similarly, the interpretation of other label free imaging techniques, such as simulated Raman scattering (SRS) microscopy and optical coherence tomography (OCT), has been qualitatively linked to H&E stained images [20,21,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCT provides microscopic structural imaging. It has been used to detect brain cancer based on optical attenuation (14). RS provides vibrational molecular information based on inelastic light scattering from molecular species, including amino acids, lipids, proteins, and nucleic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, variations in collagen orientation and content was also exploited to differentiate cancerous tissue from healthy ex vivo breast tissue using polarization-sensitive OCT [163]. Alternatively, Kut et al demonstrated that tissue scattering coefficients estimated from OCT volumes could be used to quantitatively differentiate between cancerous and noncancerous tissue and help guide brain tumor resections [164]. A color-coded map denoting regions of high scattering and low scattering, corresponding to healthy and normal tissue, respectively, was generated in real-time to provide visual feedback to the surgeon (Fig.…”
Section: Intraoperative Oct Adjunctsmentioning
confidence: 99%